Do deficits in the magnocellular priming underlie visual derealization phenomena?: preliminary neurophysiological and self-report results in first-episode schizophrenia patients - Nunez, Daniel; Oelkers-Ax, Rieke; Haan, Sanneke de; Ludwig, Max; Resch, Franz; Weisbrod, Matthias; Fuchs, Thomas (Schizophrenia research, 2014)
Background: Early visual impairments probably partially caused by impaired interactions between magnocellular (M) and parvocellular (P) pathways (M priming deﬁcit), and disturbances of basic self-awareness or self-disorders (SDs) are core features of schizophrenia. The relationships between these features have not yet been studied. We hypothesized that the M priming was impaired in ﬁrst-episode patients and that this deﬁcit was associated with visual aspects of SDs. Aim: To investigate early visual processing in a sample of ﬁrst-episode schizophrenia patients and to explore the relationships between M and P functioning and visual aspects of SDs addressed by the Examination of Anomalous Self-Experience (EASE) interview. - Method: Nine stimulating conditions were used to investigate M and P pathways and their interaction in a pattern reversal visually evoked potential (VEP) paradigm. N80 at mixed M- and P-conditions was used to investigate magnocellular priming. Generators were analyzed using source localization (Brain Electrical Source Analysis software: BESA). VEPs of nineteen ﬁrst-episode schizophrenia patients were compared to those of twenty matched healthy controls by a bootstrap resample procedure. Visual aspects of SDs were analyzed through a factor analysis to separate symptom clusters of derealization phenomena. Thereafter, the associations between the main factors and the N80 component were explored using linear mixed models. - Results: Factor analyses separated two EASE factors (“distance to the world”, and “intrusive world”). The N80 component was represented by a single dipole located in the occipital visual cortex. The bootstrap analysis yielded signiﬁcant amplitude reductions and prolonged latencies in ﬁrst-episode patients relative to controls in response to mixed M-P conditions, and normal amplitudes and latencies in response to isolated P- and M-biased stimulation. Exploratory analyses showed signiﬁcant negative correlations between the N80 amplitude values at mixed M-P conditions and the EASE factor “distance to the world”, i.e. relatively higher amplitudes in the patient group were associated with higher subjective perceived derealization (“distance to the world”). - Conclusions: The early VEP component N80 evoked by mixed M-P conditions is assumed to be a correlate of M priming, and showed reduced amplitudes and longer latencies in ﬁrst-episode patients. It probably reﬂects a hypoactivation of the M-pathway. The negative association between visual SDs (derealization phenomena characterized by visual experiences of being more distant to the world), and the M priming deﬁcit was counterintuitive. It might indicate a dysregulated activity of the M-pathway in patients with SDs. Further research is needed to better understand this preliminary ﬁnding.
Gesehen am 08.09.2020